Environmental evolution of the Basque Coast Geopark estuaries (southern Bay of Biscay) during the last 10,000 years - Cearreta, Alejandro; Irabien, María Jesús; Arozamena, José E. Gómez; El Bani Altuna, Naima; Goffard, Aintzane; García-Artola, Ane (Journal of Marine Systems, 2021)
In order to reconstruct the environmental evolution of the Deba and Urola estuaries located in the Basque Coast Geopark at millennial, centennial and decadal timescales, four long boreholes, three short cores and twelve surface samples were studied. Multiproxy analysis (foraminifera, trace metals and radioisotopes) shows the temporal transformation of these estuaries in response to regional driving forces such as fresh-water discharge, relative sea-level (RSL) variation and the more recent impact of industrial development. At millennial and centennial timescales, the Deba estuary transformed from a tide-dominated to a river-dominated estuary at about 8000 yr cal BP following the decrease in RSL rise rate. This decrease also led to a reduction in both salinity and marine influence in the nearby tide-dominated Urola estuary. At decadal timescale, human disturbance on foraminiferal populations was found to be lower in the Deba estuary despite its higher level of contaminants in sediments. This was due to the greater impact of fresh-water discharge. In the Urola estuary, dredging operations altered severely the foraminiferal biota.